Recent Advancements in the Regeneration of Auditory Hair Cells and Hearing Restoration - Mittal, Rahul; Nguyen, Desiree; Patel, Amit P.; Debs, Luca H.; Mittal, Jeenu; Yan, Denise; Eshraghi, Adrien A.; Van De Water, Thomas R.; Liu, Xue Z. (Frontiers in Molecular Neuroscience, 2017)
Neurosensory responses of hearing and balance are mediated by receptors in specialized neuroepithelial sensory cells. Any disruption of the biochemical and molecular pathways that facilitate these responses can result in severe deficits, including hearing loss and vestibular dysfunction. Hearing is affected by both environmental and genetic factors, with impairment of auditory function being the most common neurosensory disorder affecting 1 in 500 newborns, as well as having an impact on the majority of elderly population. Damage to auditory sensory cells is not reversible, and if sufficient damage and cell death have taken place, the resultant deficit may lead to permanent deafness. Cochlear implants are considered to be one of the most successful and consistent treatments for deaf patients, but only offer limited recovery at the expense of loss of residual hearing. Recently there has been an increased interest in the auditory research community to explore the regeneration of mammalian auditory hair cells and restoration of their function. In this review, we examine a variety of recent therapies, including genetic, stem cell, and molecular therapies as well as discussing progress being made in genome editing strategies as applied to the restoration of hearing function.